RETRACTED: Features of accounting for nonlinear work of reinforced concrete in calculations - Makhmudov Said; Askarova Mukhlisa Bakhromjon; Xasanov Davlatbek; Askarov Xasanjon (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001